Factors of International Activity of Russian Cities: The Results of the Empirical Analysis - R. S. Mukhametov (Vestnik MGIMO-Universiteta)
The international activities of governments at the subnational level have become widespread practice. Cooperation between local authorities, which began in Europe with the aim of promoting peace, international understanding, and reconciliation between peoples in the post-war period, has spread throughout the world over time. International cityto- city partnerships, also known as sister cities, have become an instrument for promoting economic development. The movement of sister cities is considered not only as a form of cross-border intermunicipal cooperation, but also as one of the aspects of paradiplomacy. One of the consequences of regionalization that swept post-Soviet Russia in the 1990s was the growth of foreign economic activity, international contacts of both Russian regions and cities. This is reflected in the signing of intermunicipal agreements. This research is aimed at determining the factors on which the international activity of Russian cities depends. The theoretical and methodological basis of the work was the concept of paradiplomacy in general and city diplomacy in particular. The author put forward several hypotheses in the framework of the approaches to high international activity of cities existing in the scientific literature. The database was a list of sister cities, including 150 Russian municipalities compiled by the International Association of Related Cities. Statistical calculations were performed by multiple linear regression. As a result of the study, it was found that a large number of sister cities are observed in Russian cities, which can be attributed to megacities and large cities. It was revealed that a high level of international activity of Russian cities is characteristic of municipalities located in border regions. It is shown that economic characteristics directly affect the number of contracts. The author came to the conclusion that the status of the administrative center of Russian regions positively affects on the number of sister cities. The article emphasizes the influence of the historical heritage of territories on the development of inter-municipal cultural cooperation. In conclusion, it is noted that the influence of demographic, geographical, economic, political, legal, and cultural-historical features of municipalities on the number of sister cities does not explain all cases. The author believes that the political factor has a certain explanatory power.